An integrated GIS data model for hydrological information system - 210886 Daut Daman; Harihodin Selamat; Mohd. Shafry Mohd. Rahim; Source Water Protection Symposium : A United Approach (2001 : Georgia) (Skudai : Universiti Teknologi Malaysia, 2001)
07